Resourceful co-treatment process for overhaul slag of electrolytic aluminum carbon slag

Through multi-stage crushing, flotation-leaching coupling, gradient oxidation and cyanide removal, dynamic solid fluorine and aluminum lithium directional recovery technologies, the problems of low resource recovery rate and environmental protection requirements in the resource treatment of electrolytic aluminum overhaul slag are solved, efficient resource recovery and environmental protection effects are achieved, and the cost of steel smelting is reduced.

CN120463223APending Publication Date: 2025-08-12SHANXI HUAXING ECOLOGICAL TECHNOLOGY CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510601144.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-12
Publication Date
2025-08-12

AI Technical Summary

Technical Problem

The prior art is difficult to effectively deal with electrolytic aluminum overhaul slag, resulting in low resource recovery rate and difficult to meet environmental protection requirements, and traditional methods have the risk of secondary pollution.

Method used

Multi-stage crushing, flotation-leaching coupling, gradient oxidation and cyanide removal, dynamic solid fluorine and aluminum lithium directed recovery technology are adopted. Through the coordinated oxidation of calcium hypochlorite and hydrogen peroxide, PAC acidification and hydrolysis and aluminum lithium directed recovery, the cyanide removal rate is >99.5%, and the lithium recovery rate is ≥93%. The crude calcium fluoride is directly used in steel smelting.

Benefits of technology

The harmless rate of hazardous waste is ≥99.8%, the cyanide leaching concentration is <1mg/L, the carbon recovery rate is ≥92%, the aluminum recovery rate is ≥96%, and the lithium recovery rate is ≥93%, reducing the cost of steel smelting by 15-20%, shortening the slag time by more than 30%, and improving economic benefits by 50%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120463223A_ABST
    Figure CN120463223A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of dangerous waste recycling, in particular to an electrolytic aluminum carbon slag overhaul slag recycling cooperative treatment process. According to the synergistic treatment process for the electrolytic aluminum carbon residues and the overhaul residues, hazardous wastes are converted into carbon powder, regenerated electrolyte, industrial salt, lithium carbonate and a high-value deoxidizer through the technologies of multi-stage crushing, flotation-leaching coupling, gradient oxidation cyanogen removal, dynamic fluorine fixation and directional aluminum and lithium recovery. Calcium hypochlorite-hydrogen peroxide synergistic oxidation, PAC acidification hydrolysis aluminum recovery and a crude calcium fluoride deoxidizing agent formula are creatively utilized, and the cyanide removal rate gt is achieved; the lithium recovery rate is larger than or equal to 93%, the crude calcium fluoride is directly used for iron and steel smelting, and the use amount of fluorite is reduced by 20%. The method has environment-friendly compliance and economic benefits, and is suitable for recycling and upgrading of hazardous wastes in the electrolytic aluminum industry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of hazardous waste resource utilization, and in particular to a collaborative processing process for resource utilization of electrolytic aluminum carbon slag and overhaul slag. Background Art

[0002] During the aluminum electrolysis process, overhaul slag and carbon slag are the most typical hazardous wastes in the electrolytic aluminum industry. They are all listed on the National Hazardous Waste Catalogue published by the Ministry of Ecology and Environment. Their main hazardous characteristics include toxicity and reactivity. During the harmless disposal of hazardous wastes, such as leaching, filtration, and washing, improper disposal of the leachate, filtrate, or washing liquid can cause secondary pollution.

[0003] Overhaul slag is the waste residue generated by the maintenance and replacement of the cathode lining of the electrolytic cell during the electrolytic aluminum production process. The electrolytic aluminum industry produces millions of tons of carbon residue (SCA) and overhaul slag (SPL) every year. The combined pollution characteristics of fluoride (15-26%), cyanide (≤2‰) and graphite carbon (35-55%) make it a high-hazard solid waste.

[0004] At present, there is a contradiction between the efficiency of fluorine-aluminum separation and energy consumption. The conventional lime precipitation method produces CaF2 with low purity and requires excessive addition of Ca. 2+ , resulting in an increase in sludge production (3-5 tons of waste slag per ton of slag), while crude calcium fluoride (CaF2>25%) has a high impurity content (Al 3+ >0.5%), it cannot be directly used as a deoxidizer in steelmaking, limiting the benefits of resource utilization.

[0005] Extensive research has been conducted on the disposal and comprehensive resource utilization of aluminum electrolytic overhaul slag, which is generally categorized into two main types: wet treatment and pyrolysis. Traditional pyrolysis processes do not completely detoxify and cannot fully recover resources. Wet treatment processes, which primarily include water leaching, alkaline leaching, acid leaching, and combined acid-base leaching, achieve harmless treatment of the entire aluminum electrolytic overhaul slag. However, the acid and alkaline leaching processes generate acid and alkaline leaching solutions that are simply neutralized to recover precipitated aluminum fluoride, resulting in low efficiency.

[0006] For example, CN112094923A discloses a carbon slag flotation process, but does not solve the problem of cyanide residue; CN113526765A proposes an overhaul slag alkali leaching method, but the aluminum and lithium recovery rate is insufficient, and the SCA process is not used in conjunction; CN114456851A uses calcium hypochlorite to remove cyanide, but does not combine it with hydrogen peroxide for synergistic oxidation, resulting in a cyanide removal rate of less than 95%.

[0007] Existing technologies are difficult to meet resource recovery and increasingly stringent environmental protection requirements. There is an urgent need for a resource processing method for aluminum electrolysis overhaul slag to solve the problems existing in the existing technology for overhaul slag recycling. Summary of the Invention

[0008] The purpose of the present invention is to solve the shortcomings of the prior art and to propose a resource-based collaborative treatment process for electrolytic aluminum carbon slag and overhaul slag.

[0009] A collaborative processing process for recycling electrolytic aluminum carbon slag and overhaul slag includes the following steps:

[0010] S1. Crushing the carbon slag to a particle size of <10 mm, wet ball milling, and flotation separation to obtain coarse carbon powder and regenerated electrolyte raw material slurry; deeply defluorinating the coarse carbon powder with calcium hydroxide to obtain defluorinated carbon powder; filtering the regenerated electrolyte raw material slurry to obtain a saturated flotation solution;

[0011] S2. Dry-grind the overhaul slag into powder, add the saturated flotation solution obtained in S1 and evaporated condensed water, adjust the solid-liquid ratio of the system to 1:2.5-3.0, and then carry out oxidation and cyanide removal and dynamic fluoride fixation treatment in sequence to obtain crude calcium fluoride and filtrate;

[0012] In the obtained crude calcium fluoride, the mass percentage of calcium fluoride is greater than 25%, and the mass percentage of carbon is greater than 35%;

[0013] S3, using polyaluminum chloride to remove aluminum from the filtrate obtained in S2 under acidification conditions, concentrating it using steam mechanical recompression technology to obtain industrial salt and concentrated liquid, and precipitating the concentrated liquid to obtain lithium carbonate;

[0014] S4. The crude calcium fluoride obtained in S2, aluminum powder and rare earth oxide are mixed in a mass ratio of 96-97.5:2-3:0.5-1 to obtain a LF furnace deoxidizer.

[0015] Preferably, in the crushing process in S1, a jaw crusher is used for coarse crushing to a particle size of <100 mm, and then a hammer crusher is used for fine crushing to a particle size of <10 mm.

[0016] Preferably, during the wet ball milling slurrying process in S1, the mass fraction of the slurry is adjusted to 25-35%, and then sodium polyacrylate is added thereto and the slurry is milled for 30-45 minutes, and the mass ratio of sodium polyacrylate to slurry is 0.1-0.3:99.7-99.9.

[0017] Preferably, during the flotation separation process in S1, a diesel collector and MIBC foaming agent are added to the system, the amount of the diesel collector added is 0.5-1.2 kg / t, and the amount of the MIBC foaming agent added is 0.05-0.1 kg / t; and the speed of the mechanical stirring flotation machine is adjusted to 280-320 r / min.

[0018] Preferably, during the flotation separation process in S1, the recovery rate of coarse carbon powder is ≥92%.

[0019] Preferably, during the deep defluorination process in S1, the mass ratio of calcium hydroxide to coarse carbon powder is 2-4:96-98, the system pH is 8.5-9.0, the deep defluorination reaction temperature is 60-70°C, and the fluoride ion leaching concentration of the defluorinated carbon powder is <80 mg / L.

[0020] S1 belongs to the process of carbon slag flotation technology, and its process complies with the "YS / T 1400-2020 Specification for Resource Utilization of Aluminum Electrolysis Anode Carbon Slag". Through this process, the effective separation and resource utilization of carbon slag can be achieved.

[0021] Preferably, the particle size of the overhaul slag used in S2 is less than 10 mm.

[0022] Preferably, after the oxidation and decyanation in S2, the cyanide removal rate in the system is greater than 99.5%.

[0023] Preferably, in S2, calcium hypochlorite is used for oxidation and cyanide removal, or calcium hypochlorite and hydrogen peroxide are used in sequence for oxidation and cyanide removal.

[0024] Preferably, in S2, after adjusting the solid-liquid ratio of the system to 1:2.5-3.0, calcium hypochlorite is added to the system, and the molar ratio of calcium hypochlorite to cyanide ion is 1.1-1.3:1. The pH value of the system is adjusted to 10-11, and the reaction is stirred for 30-50 minutes.

[0025] More preferably, if the cyanide removal rate in the system after adding calcium hypochlorite is ≤99.5%, 0.5-1.0% hydrogen peroxide is added in portions, the pH value of the system is adjusted to 10-11, and the reaction is stirred for 10-30 minutes until the cyanide removal rate in the system is greater than 99.5%.

[0026] The purpose of this step is to remove cyanide by oxidation and generate calcium carbonate.

[0027] 4CN - +5Ca(OCl)2+2H2O=N2↑+3CaCl2+2Ca(HCO3)2+4Cl -

[0028] 2Ca(ClO)2+4H2O2+2CN - =2CaCO3↓+2Cl - +N2↑+4H2O

[0029] Ca(HCO3)2+2OH - =CaCO3↓+2H2O+CO3 2-

[0030] Preferably, the dynamic fluorine fixation treatment in S2 is specifically performed as follows: adding excess calcium chloride and excess calcium hydroxide to the system after oxidation and cyanide removal in sequence, and adjusting the pH value to 7.5-8.5 with hydrochloric acid.

[0031] Hydrochloric acid is used to adjust the pH to around 8. The dissolution rate of calcium fluoride gradually decreases as it approaches thermodynamic equilibrium, and calcium carbonate is converted into calcium fluoride under this condition.

[0032] CaCO3+2HCl=CaCl2+CO2↑+H2O

[0033] CaCO3+2F - +H2O=CaF2↓+CO2↑+2OH -

[0034] CaCl2+2F - =CaF2↓+2Cl -

[0035] Preferably, the dynamic fluorine fixation treatment in S2 is specifically performed as follows: adding excess calcium chloride, sodium phosphate, nano calcium fluoride seeds and excess calcium hydroxide to the system after oxidation and cyanide removal, adjusting the pH value to 7.5-8.5, and performing pulse ultrasonic treatment for 3-6 minutes, with a duty cycle of 50%, an ultrasonic frequency of 30-40kHz, and an acoustic intensity of 0.6-0.8W / cm 2 .

[0036] In the above-mentioned dynamic fluorine fixation process of the present invention, ultrasonic enhancement is used to promote rapid collision between calcium ions and fluoride ions, resulting in a fast nucleation rate. Sodium phosphate has a guiding effect, and phosphate groups preferentially occupy calcium fluoride lattice defect sites through surface adsorption. The formation of Ca-P complexes reduces the ΔG crystallization free energy, promotes the preferential precipitation of calcium fluoride, inhibits aluminum ion doping, and effectively improves the extraction efficiency of crude calcium fluoride. At the same time, intermittent high-pressure shock waves are generated during the crystal growth stage, which can not only destroy the impurity adsorption layer but also inhibit dendrite growth, forming dense spherical calcium fluoride particles, reducing porosity, and compounding with aluminum powder and rare earth oxides to control the ratio, thereby greatly improving the furnace desulfurization rate and effectively shortening the slagging time.

[0037] More preferably, the molar ratio of sodium phosphate, nano-calcium fluoride seeds and fluoride ions is 0.6-0.8:0.01-0.1:2.

[0038] Preferably, in S3, the specific operation of aluminum removal is as follows: polyaluminum chloride and hydrochloric acid with a pH of 4.0-4.5 are added to the filtrate obtained in S2, and the mass volume ratio of polyaluminum chloride to the filtrate obtained in S2 is 10-15 g / L.

[0039] The main component of the filtrate after removing calcium fluoride is NaCl, and the main impurities are various forms of hydrated / polymerized sodium aluminate salts formed during alkaline leaching; adding polyaluminum chloride PAC and hydrochloric acid can produce an in-situ hydrolysis reaction, forming an acidic environment on the surface of PAC, thereby pulling the sodium aluminate to depolymerize and eventually hydrolyze and convert it into aluminum hydroxide, which is removed by filtration.

[0040]

[0041] Al(OH)4 - +H + =Al(OH)3↓+H2O

[0042] OH - +H + =H2O

[0043] Preferably, the evaporation temperature in the concentration process in S3 is 70-80°C, the vacuum degree is -0.08 to -0.06 MPa, and the density of the concentrated liquid is 1.25-1.30 g / cm 3 .

[0044] Preferably, in S3, the purity of lithium carbonate obtained by precipitating the concentrated liquid is ≥99.5%, and the lithium recovery rate is ≥93%.

[0045] Preferably, in S3, the concentrated liquid is precipitated with a soluble carbonate, the molar ratio of carbonate ions to lithium ions in the soluble carbonate is 1:2, the pH of the system is adjusted to 8.0-8.5, and the precipitation time is 1-22 hours.

[0046] 2Li + +CO3 2- =Li2CO3

[0047] Preferably, in S3, the concentrated liquid is precipitated by introducing carbon dioxide at a rate of 0.5-1.0 L / min, and the pH value of the system is adjusted to 6.5-7.0.

[0048] 2Li + +CO2+H2O=Li2CO3+2H +

[0049] Preferably, in S4, the rare earth oxide is cerium oxide and / or lanthanum oxide.

[0050] Beneficial effects:

[0051] 1. The present invention reuses SCA flotation fluid for overhaul slag slurry adjustment, achieving a water-reagent closed-loop cycle and reducing fresh water consumption by more than 30%. Gradient oxidation and dynamic fluoride fixation technologies ensure that cyanide and fluoride levels meet standards simultaneously (cyanide ion content <5 mg / L, fluoride ion content <100 mg / L). At the same time, crude calcium fluoride deoxidizer is used to replace traditional fluorite, increasing the desulfurization rate by more than 25%, shortening the slagging time by more than 30%, and reducing steelmaking costs by 15-20%.

[0052] 2. Environmental protection indicators: The hazardous waste harmlessness rate of the present invention is ≥99.8%, and the cyanide leaching concentration is <1mg / L;

[0053] 3. Resource recovery rate: The carbon recovery rate of the present invention is ≥92%, the aluminum recovery rate is ≥96%, and the lithium recovery rate is ≥93%;

[0054] 4. Economic benefits: The present invention reduces the processing cost per ton by 40% and increases the added value of the product by 50%.

[0055] 5. The collaborative treatment process of this invention utilizes multi-stage crushing, coupled flotation-leaching, gradient oxidation cyanide removal, dynamic fluoride fixation, and directional aluminum and lithium recovery technologies to achieve a cyanide removal rate of >99.5% and a lithium recovery rate of ≥93%. The crude calcium fluoride can be directly used in steelmaking, reducing fluorite usage by 20%. This invention combines environmental compliance with economic benefits and is suitable for resource recovery of hazardous waste in the electrolytic aluminum industry. BRIEF DESCRIPTION OF THE DRAWINGS

[0056] Figure 1 This is a comparison chart of the desulfurization improvement rate and slagging time shortening rate when the LF furnace deoxidizers obtained by Example 1, Example 2 and Comparative Examples 1-2 are used in ladle refining. DETAILED DESCRIPTION

[0057] The present invention will be further explained below with reference to specific embodiments.

[0058] Carbon slag and overhaul slag were obtained from a factory of China Aluminum Corporation. The carbon slag included, by mass percentage, the following components: SiO2 0.21%, Fe 0.14%, C 45.6%, Na 18.2%, F 26.1%, Al 6.24%, P 0.02%, and others 3.49%; while the overhaul slag included, by mass percentage, the following components: C 55%, Na 20%, F 15%, and Al2O3 10%.

[0059] Example 1

[0060] A collaborative processing process for recycling electrolytic aluminum carbon slag and overhaul slag includes the following steps:

[0061] S1. Use jaw crusher to crush carbon slag to particle size <100mm, then use hammer crusher to crush it to particle size <10mm;

[0062] The crushed carbon residue was made into a slurry, and the mass fraction of the slurry was adjusted to 30%. Then, sodium polyacrylate was added thereto and wet ball milled for 40 minutes. The mass ratio of sodium polyacrylate to slurry was 0.2:99.8.

[0063] The ball-milled slurry was added to a mechanical agitation flotation machine, and then a collector (diesel, added at a rate of 1 kg / t) and a frother (MIBC, added at a rate of 0.08 kg / t) were added. The speed of the mechanical agitation flotation machine was set at 300 rpm, and flotation separation was performed to obtain coarse carbon powder (with a recovery rate of 94.2%) and regenerated electrolyte raw material slurry;

[0064] The obtained regenerated electrolyte raw material slurry includes, by mass percentage: F 51.2%, Al 12.5%, Na 33.2%, Fe2O3 0.21%, SiO2 0.44%, P2O5 0.02%, and C 2.43%;

[0065] Calcium hydroxide and coarse carbon powder were mixed in a mass ratio of 3:97, the pH value of the system was adjusted to 8.5-9.0, the temperature was maintained at 65°C, and defluorinated carbon powder (fluoride ion leaching concentration was 61 mg / L) was obtained by deep defluorination;

[0066] The regenerated electrolyte raw material slurry is filtered to obtain a saturated flotation solution, and the water produced during the flotation process can be recycled;

[0067] S2, dry-grind overhaul slag with a particle size of less than 10 mm into powder, add the saturated flotation liquid obtained in S1 and evaporated condensed water, and adjust the solid-liquid ratio of the system to 1:2.8;

[0068] Calcium hypochlorite was added to the system at a molar ratio of calcium hypochlorite to cyanide ion of 1.2:1, the pH value of the system was adjusted to 10-11, and the reaction was stirred for 40 minutes;

[0069] Then, 0.8% hydrogen peroxide was added in batches, the pH value of the system was adjusted to 10-11, and the reaction was stirred for 20 minutes. - The residual concentration is 0.8 mg / L;

[0070] adding an excess of calcium chloride (1.1 times the theoretical amount calculated based on the free fluoride ion content in the system) and an excess of calcium hydroxide (10% excess) to the system after cyanide removal, and adjusting the pH to 7.5-8.5 with hydrochloric acid to obtain crude calcium fluoride (wherein the mass percentage of calcium fluoride is 25.79% and the mass percentage of carbon is 36.75%) and a filtrate;

[0071] S3, add polyaluminium chloride and hydrochloric acid with pH=4.0-4.5 to the filtrate obtained in S2, the mass volume ratio of polyaluminium chloride to the filtrate obtained in S2 is 12g / L; use MVR to concentrate to obtain industrial salt and density 1.28g / cm 3 The concentrated liquid, MVR evaporation temperature is 75℃, vacuum degree is -0.07MPa;

[0072] Carbon dioxide was introduced into the concentrated liquid (at a rate of 0.8 L / min), and the pH value of the system was adjusted to 6.5-7.0 to precipitate lithium carbonate (with a purity of 99.6%).

[0073] S4. The crude calcium fluoride, aluminum powder and cerium oxide obtained in S2 are mixed in a mass ratio of 97:2.5:0.5 to obtain a LF furnace deoxidizer.

[0074] Example 2

[0075] A collaborative processing process for recycling electrolytic aluminum carbon slag and overhaul slag includes the following steps:

[0076] S1. Use jaw crusher to crush carbon slag to particle size <100mm, then use hammer crusher to crush it to particle size <10mm;

[0077] The crushed carbon residue was made into a slurry, and the mass fraction of the slurry was adjusted to 30%. Then, sodium polyacrylate was added thereto and wet ball milled for 40 minutes. The mass ratio of sodium polyacrylate to slurry was 0.2:99.8.

[0078] The ball-milled slurry was added to a mechanical agitation flotation machine, and then a collector (diesel, added at a rate of 1 kg / t) and a frother (MIBC, added at a rate of 0.08 kg / t) were added. The speed of the mechanical agitation flotation machine was set at 300 rpm, and flotation separation was performed to obtain coarse carbon powder (with a recovery rate of 94.2%) and regenerated electrolyte raw material slurry;

[0079] The obtained regenerated electrolyte raw material slurry includes, by mass percentage: F 51.2%, Al 12.5%, Na 33.2%, Fe2O3 0.21%, SiO2 0.44%, P2O5 0.02%, and C 2.43%;

[0080] Calcium hydroxide and coarse carbon powder were mixed in a mass ratio of 3:97, the pH value of the system was adjusted to 8.5-9.0, the temperature was maintained at 65°C, and defluorinated carbon powder was obtained by deep defluorination (fluoride ion leaching concentration was 61 mg / L);

[0081] The regenerated electrolyte raw material slurry is filtered to obtain a saturated flotation solution, and the water produced during the flotation process can be recycled;

[0082] S2, dry-grind overhaul slag with a particle size of less than 10 mm into powder, add the saturated flotation liquid obtained in S1 and evaporated condensed water, and adjust the solid-liquid ratio of the system to 1:2.8;

[0083] Calcium hypochlorite was added to the system at a molar ratio of calcium hypochlorite to cyanide ion of 1.2:1, the pH value of the system was adjusted to 10-11, and the reaction was stirred for 40 minutes;

[0084] Then, 0.8% hydrogen peroxide was added in batches, the pH value of the system was adjusted to 10-11, and the reaction was stirred for 20 minutes. - The residual concentration is 0.8 mg / L;

[0085] After the cyanide is removed, excess calcium chloride (1.1 times the theoretical amount calculated by the free fluoride ion content in the system), sodium phosphate, and nano calcium fluoride seeds (D 50 =1-1.5 μm) and excess calcium hydroxide (excess 10%), the molar ratio of sodium phosphate, nano calcium fluoride seeds and fluoride ions is 0.7:0.05:2; the pH value is adjusted to 7.5-8.5, and pulse ultrasonic treatment is performed for 5 minutes, with a duty cycle of 50%, an ultrasonic frequency of 36 kHz, and an acoustic intensity of 0.7 W / cm 2 , obtaining crude calcium fluoride (wherein the mass percentage of calcium fluoride is 29.63% and the mass percentage of carbon is 38.11%) and filtrate;

[0086] S3, add polyaluminium chloride and hydrochloric acid with pH=4.0-4.5 to the filtrate obtained in S2, the mass volume ratio of polyaluminium chloride to the filtrate obtained in S2 is 12g / L; use MVR to concentrate to obtain industrial salt and density 1.28g / cm 3 The concentrated liquid, MVR evaporation temperature is 75℃, vacuum degree is -0.07MPa;

[0087] Sodium carbonate was added to the concentrated liquid at a molar ratio of sodium carbonate to lithium ions of 1:2. The pH of the system was adjusted to 8.0-8.5, and the precipitation time was 2 hours to obtain lithium carbonate (purity of 99.7%).

[0088] S4. The crude calcium fluoride, aluminum powder and cerium oxide obtained in S2 are mixed in a mass ratio of 96.8:2.5:0.7 to obtain a LF furnace deoxidizer.

[0089] Comparative Example 1

[0090] A collaborative processing process for recycling electrolytic aluminum carbon slag and overhaul slag includes the following steps:

[0091] S1. Use jaw crusher to crush carbon slag to particle size <100mm, then use hammer crusher to crush it to particle size <10mm;

[0092] The crushed carbon residue was made into a slurry, and the mass fraction of the slurry was adjusted to 30%. Then, sodium polyacrylate was added thereto and wet ball milled for 40 minutes. The mass ratio of sodium polyacrylate to slurry was 0.2:99.8.

[0093] The ball-milled slurry was added to a mechanical agitation flotation machine, and then a collector (diesel, added at a rate of 1 kg / t) and a frother (MIBC, added at a rate of 0.08 kg / t) were added. The speed of the mechanical agitation flotation machine was set at 300 rpm, and flotation separation was performed to obtain coarse carbon powder (with a recovery rate of 94.2%) and regenerated electrolyte raw material slurry;

[0094] The obtained regenerated electrolyte raw material slurry includes, by mass percentage: F 51.2%, Al 12.5%, Na 33.2%, Fe2O3 0.21%, SiO2 0.44%, P2O5 0.02%, and C 2.43%;

[0095] Calcium hydroxide and coarse carbon powder were mixed in a mass ratio of 3:97, the pH value of the system was adjusted to 8.5-9.0, the temperature was maintained at 65°C, and defluorinated carbon powder was obtained by deep defluorination (fluoride ion leaching concentration was 61 mg / L);

[0096] The regenerated electrolyte raw material slurry is filtered to obtain a saturated flotation solution, and the water produced during the flotation process can be recycled;

[0097] S2, dry-grind overhaul slag with a particle size of less than 10 mm into powder, add the saturated flotation liquid obtained in S1 and evaporated condensed water, and adjust the solid-liquid ratio of the system to 1:2.8;

[0098] Calcium hypochlorite was added to the system at a molar ratio of calcium hypochlorite to cyanide ion of 1.2:1, the pH value of the system was adjusted to 10-11, and the reaction was stirred for 40 minutes;

[0099] Then, 0.8% hydrogen peroxide was added in batches, the pH value of the system was adjusted to 10-11, and the reaction was stirred for 20 minutes. - The residual concentration is 0.8 mg / L;

[0100] After the cyanide is removed, excess calcium chloride (1.1 times the theoretical amount calculated by the free fluoride ion content in the system), sodium phosphate, and nano calcium fluoride seeds (D 50 =1-1.5 μm) and excess calcium hydroxide (excess 10%), a molar ratio of sodium phosphate, nano calcium fluoride seeds, and fluoride ions of 0.7:0.05:2; adjusting the pH value to 7.5-8.5, performing ultrasonic treatment for 5 minutes at an ultrasonic frequency of 36 kHz to obtain crude calcium fluoride (wherein the mass percentage of calcium fluoride is 26.85% and the mass percentage of carbon is 37.45%) and a filtrate;

[0101] S3, add polyaluminium chloride and hydrochloric acid with pH=4.0-4.5 to the filtrate obtained in S2, the mass volume ratio of polyaluminium chloride to the filtrate obtained in S2 is 12g / L; use MVR to concentrate to obtain industrial salt and density 1.28g / cm 3 The concentrated liquid, MVR evaporation temperature is 75℃, vacuum degree is -0.07MPa;

[0102] Sodium carbonate was added to the concentrated liquid at a molar ratio of sodium carbonate to lithium ions of 1:2. The pH of the system was adjusted to 8.0-8.5, and the precipitation time was 2 hours to obtain lithium carbonate (purity of 99.7%).

[0103] S4. The crude calcium fluoride, aluminum powder and cerium oxide obtained in S2 are mixed in a mass ratio of 96.8:2.5:0.7 to obtain a LF furnace deoxidizer.

[0104] Comparative Example 2

[0105] A collaborative processing process for recycling electrolytic aluminum carbon slag and overhaul slag, comprising the following steps:

[0106] S1. Use jaw crusher to crush carbon slag to particle size <100mm, then use hammer crusher to crush it to particle size <10mm;

[0107] The crushed carbon residue was made into a slurry, and the mass fraction of the slurry was adjusted to 30%. Then, sodium polyacrylate was added thereto and wet ball milled for 40 minutes. The mass ratio of sodium polyacrylate to slurry was 0.2:99.8.

[0108] The ball-milled slurry was added to a mechanical agitation flotation machine, and then a collector (diesel, added at a rate of 1 kg / t) and a frother (MIBC, added at a rate of 0.08 kg / t) were added. The speed of the mechanical agitation flotation machine was set at 300 rpm, and flotation separation was performed to obtain coarse carbon powder (with a recovery rate of 94.2%) and regenerated electrolyte raw material slurry;

[0109] The obtained regenerated electrolyte raw material slurry includes, by mass percentage: F 51.2%, Al 12.5%, Na 33.2%, Fe2O3 0.21%, SiO2 0.44%, P2O5 0.02%, and C 2.43%;

[0110] Calcium hydroxide and coarse carbon powder were mixed in a mass ratio of 3:97, the pH value of the system was adjusted to 8.5-9.0, the temperature was maintained at 65°C, and defluorinated carbon powder (fluoride ion leaching concentration was 61 mg / L) was obtained by deep defluorination;

[0111] The regenerated electrolyte raw material slurry is filtered to obtain a saturated flotation solution, and the water produced during the flotation process can be recycled;

[0112] S2, dry-grind overhaul slag with a particle size of less than 10 mm into powder, add the saturated flotation liquid obtained in S1 and evaporated condensed water, and adjust the solid-liquid ratio of the system to 1:2.8;

[0113] Calcium hypochlorite was added to the system at a molar ratio of calcium hypochlorite to cyanide ion of 1.2:1, the pH value of the system was adjusted to 10-11, and the reaction was stirred for 40 minutes;

[0114] Then, 0.8% hydrogen peroxide was added in batches, the pH value of the system was adjusted to 10-11, and the reaction was stirred for 20 minutes. - The residual concentration is 0.8 mg / L;

[0115] After the cyanide is removed, excess calcium chloride (1.1 times the theoretical amount calculated by the free fluoride ion content in the system), nano calcium fluoride seeds (D 50 =1-1.5 μm) and excess calcium hydroxide (excess 10%), the molar ratio of nano calcium fluoride seeds to fluoride ions is 0.05:2; the pH value is adjusted to 7.5-8.5, and pulse ultrasonic treatment is performed for 5 minutes, with a duty cycle of 50%, an ultrasonic frequency of 36 kHz, and an acoustic intensity of 0.7 W / cm 2 , obtaining crude calcium fluoride (wherein the mass percentage of calcium fluoride is 26.01% and the mass percentage of carbon is 37.83%) and a filtrate;

[0116] S3, add polyaluminium chloride and hydrochloric acid with pH=4.0-4.5 to the filtrate obtained in S2, the mass volume ratio of polyaluminium chloride to the filtrate obtained in S2 is 12g / L; use MVR to concentrate to obtain industrial salt and density 1.28g / cm 3 The concentrated liquid, MVR evaporation temperature is 75℃, vacuum degree is -0.07MPa;

[0117] Sodium carbonate was added to the concentrated liquid at a molar ratio of sodium carbonate to lithium ions of 1:2. The pH of the system was adjusted to 8.0-8.5, and the precipitation time was 2 hours to obtain lithium carbonate (purity of 99.7%).

[0118] S4. The crude calcium fluoride, aluminum powder and cerium oxide obtained in S2 are mixed in a mass ratio of 96.8:2.5:0.7 to obtain a LF furnace deoxidizer.

[0119] Since the calcium fluoride content in the crude calcium fluoride obtained in Example 1, Example 2 and Comparative Examples 1-2 is all greater than 25%, it has the function of fluorite slag formation; and the crude calcium fluoride also contains 35-40% of graphitized carbon, which has a calorific value of more than 1000 kcal / kg. Therefore, it can be mixed with aluminum powder and cerium oxide for blast furnace slag deoxidation and promote slag foaming. It can serve the functions of deoxidation, slag formation, submerged arc, desulfurization, etc. in the molten steel refining and deoxidation process, simplify the deoxidation process of the LF refining furnace, and shorten the deoxidation and desulfurization time of the molten steel.

[0120] Therefore, the LF furnace deoxidizers obtained in Example 1, Example 2 and Comparative Examples 1-2 were used for ladle refining, and traditional fluorite was used as a control group to measure the desulfurization improvement rate and slagging time shortening rate of each group at the same addition amount.

[0121] like Figure 1 As shown, the LF furnace deoxidizer obtained in Example 2 was used for ladle refining, and the desulfurization improvement rate and slagging time shortening rate were the highest, which were better than the other groups (P < 0.05).

[0122] The above description is only a preferred specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any technician familiar with the technical field, within the technical scope disclosed by the present invention, who makes equivalent replacements or changes based on the technical solution and inventive concept of the present invention, should be covered by the scope of protection of the present invention.

Claims

1. A collaborative process for resource utilization of electrolytic aluminum carbon slag and overhaul slag, characterized in that: The steps include: S1. Crushing the carbon slag to a particle size of <10 mm, wet ball milling, and flotation separation to obtain coarse carbon powder and regenerated electrolyte raw material slurry; deeply defluorinating the coarse carbon powder with calcium hydroxide to obtain defluorinated carbon powder; filtering the regenerated electrolyte raw material slurry to obtain a saturated flotation solution; S2. Dry-grind the overhaul slag into powder, add the saturated flotation solution obtained in S1 and evaporated condensed water, adjust the solid-liquid ratio of the system to 1:2.5-3.0, and then carry out oxidation and cyanide removal and dynamic fluoride fixation treatment in sequence to obtain crude calcium fluoride and filtrate; In the obtained crude calcium fluoride, the mass percentage of calcium fluoride is greater than 25%, and the mass percentage of carbon is greater than 35%; S3, using polyaluminum chloride to remove aluminum from the filtrate obtained in S2 under acidification conditions, concentrating it using steam mechanical recompression technology to obtain industrial salt and concentrated liquid, and precipitating the concentrated liquid to obtain lithium carbonate; S4. The crude calcium fluoride obtained in S2, aluminum powder and rare earth oxide are mixed in a mass ratio of 96-97.5:2-3:0.5-1 to obtain a LF furnace deoxidizer.

2. The collaborative processing process for resource utilization of electrolytic aluminum carbon slag and overhaul slag according to claim 1 is characterized in that: During the wet ball milling slurry preparation process in S1, the mass fraction of the slurry is adjusted to 25-35%, and then sodium polyacrylate is added thereto and the slurry is milled for 30-45 minutes. The mass ratio of sodium polyacrylate to slurry is 0.1-0.3:99.7-99.

9.

3. The collaborative processing process for resource utilization of electrolytic aluminum carbon slag and overhaul slag according to claim 1 is characterized in that: During the flotation separation process in S1, diesel collector and MIBC foaming agent are added to the system. The addition amount of diesel collector is 0.5-1.2 kg / t, and the addition amount of MIBC foaming agent is 0.05-0.1 kg / t. The speed of the mechanical stirring flotation machine is adjusted to 280-320 r / min.

4. The collaborative processing process for resource utilization of electrolytic aluminum carbon slag and overhaul slag according to claim 1 is characterized in that: During the deep defluorination process in S1, the mass ratio of calcium hydroxide to coarse carbon powder is 2-4:96-98, the system pH is 8.5-9.0, the deep defluorination reaction temperature is 60-70°C, and the fluoride ion leaching concentration of the defluorinated carbon powder is <80 mg / L.

5. The collaborative processing process for resource utilization of electrolytic aluminum carbon slag and overhaul slag according to claim 1 is characterized in that: After the oxidation and decyanation in S2, the cyanide removal rate in the system is greater than 99.5%.

6. The resource-recovery collaborative treatment process of electrolytic aluminum carbon slag and overhaul slag according to claim 1 is characterized in that: In S2, calcium hypochlorite is used for oxidation and cyanide removal, or calcium hypochlorite and hydrogen peroxide are used in sequence for oxidation and cyanide removal.

7. The resource-recovery collaborative treatment process of electrolytic aluminum carbon slag and overhaul slag according to claim 6 is characterized in that: In S2, after adjusting the solid-liquid ratio of the system to 1:2.5-3.0, calcium hypochlorite is added to the system, and the molar ratio of calcium hypochlorite to cyanide ion is 1.1-1.3:

1. The pH value of the system is adjusted to 10-11, and the reaction is stirred for 30-50 minutes; If the cyanide removal rate in the system after adding calcium hypochlorite is ≤99.5%, add 0.5-1.0% hydrogen peroxide by weight in batches, adjust the pH value of the system to 10-11, and stir the reaction for 10-30 minutes until the cyanide removal rate in the system is greater than 99.5%.

8. The collaborative processing process for resource utilization of electrolytic aluminum carbon slag and overhaul slag according to claim 1 is characterized in that: The specific operation of the dynamic fluorine fixation treatment in S2 is as follows: add excess calcium chloride and excess calcium hydroxide to the system after oxidation and cyanide removal in sequence, and adjust the pH value to 7.5-8.

5.

9. The collaborative processing process for resource utilization of electrolytic aluminum carbon slag and overhaul slag according to claim 1 is characterized in that: The specific operation of the dynamic fluorine fixation treatment in S2 is as follows: add excess calcium chloride, sodium phosphate, nano calcium fluoride seeds and excess calcium hydroxide to the system after oxidation and cyanide removal, adjust the pH value to 7.5-8.5, and perform pulse ultrasonic treatment for 3-6 minutes with a duty cycle of 50%, an ultrasonic frequency of 30-40kHz, and an acoustic intensity of 0.6-0.8W / cm 2 ; The molar ratio of sodium phosphate, nano calcium fluoride crystal seeds and fluoride ions is 0.6-0.8:0.01-0.1:

2.

10. The collaborative processing process for resource utilization of electrolytic aluminum carbon slag and overhaul slag according to claim 1, characterized in that: In S3, the specific operation of aluminum removal is as follows: polyaluminum chloride and hydrochloric acid with a pH of 4.0-4.5 are added to the filtrate obtained in S2, and the mass volume ratio of polyaluminum chloride to the filtrate obtained in S2 is 10-15 g / L; During the concentration process in S3, the evaporation temperature is 70-80°C, the vacuum degree is -0.08 to -0.06 MPa, and the density of the concentrated liquid is 1.25-1.30 g / cm 3 ; In S3, the concentrated liquid is precipitated to obtain lithium carbonate with a purity of ≥99.5% and a lithium recovery rate of ≥93%; In S3, the concentrated liquid is precipitated using a soluble carbonate, the molar ratio of carbonate ions to lithium ions in the soluble carbonate is 1:2, the pH of the system is adjusted to 8.0-8.5, and the precipitation time is 1-22 hours; In S3, the concentrated liquid is precipitated by introducing carbon dioxide at a rate of 0.5-1.0 L / min, and the pH value of the system is adjusted to 6.5-7.0.

Citation Information

Patent Citations

  • SINE transposon polymorphic molecular marker related to porcine growth speed, and detection method and application of SINE transposon polymorphic molecular marker

    CN112094923A

  • Harmless co-treatment method for fly ash and electroplating wastewater

    CN113526765A

  • Green and environment-friendly coal gas desulfurization device and method

    CN114456851A

  • Composite fluorine removal agent for industrial wastewater and preparation method thereof and method for removing fluorine from industrial wastewater

    CN111547804A

  • Method for synchronously decyanating and extracting lithium from overhaul slag

    CN116814957A